1994
DOI: 10.1037/0033-295x.101.3.396
|View full text |Cite
|
Sign up to set email alerts
|

No more than skin deep: Ethnic and racial similarity in developmental process.

Abstract: Many studies adduce evidence of ethnic or racial dissimilarities in developmental outcomes (e.g., delinquency and achievement). Many researchers fail to distinguish between group average levels and developmental processes (correlations). Evidence is reviewed that developmental processes are nearly identical for U.S. Black, Hispanic, White, and Asian ethnic and racial groups. Using diverse and representative data sources, covariance matrices were computed for these ethnic groups and then compared by using a LIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
149
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(176 citation statements)
references
References 48 publications
25
149
1
1
Order By: Relevance
“…For example, comparative studies that simply examine mean differences between two ethnic groups on one or more psychological variables have been criticized on numerous grounds, including likely confounds with SES or other third variables, the focus on deviance rather than difference, and ignoring within-group variability. More preferred if one's goal is theory development are approaches that link ethnicity with the study of process, such as whether a particular set of relations is different in particular ethnic groups (see Rowe et al 1994). Ethnic differences in the relations between harsh parenting and childhood aggression (Deater-Deckard et al 1996) or between peer group influence and academic achievement (Steinberg et al 1992) are examples of studying ethnicity as a moderator of psychological process in the social domain.…”
Section: Implications For the Study Of Ethnicitymentioning
confidence: 99%
“…For example, comparative studies that simply examine mean differences between two ethnic groups on one or more psychological variables have been criticized on numerous grounds, including likely confounds with SES or other third variables, the focus on deviance rather than difference, and ignoring within-group variability. More preferred if one's goal is theory development are approaches that link ethnicity with the study of process, such as whether a particular set of relations is different in particular ethnic groups (see Rowe et al 1994). Ethnic differences in the relations between harsh parenting and childhood aggression (Deater-Deckard et al 1996) or between peer group influence and academic achievement (Steinberg et al 1992) are examples of studying ethnicity as a moderator of psychological process in the social domain.…”
Section: Implications For the Study Of Ethnicitymentioning
confidence: 99%
“…2 Correspondence should be directed to Colleen C. Pilgrim, Survey Research Center, Institute for Social Research, University of Michigan, Ann Arbor, Michigan 48106-1248; e-mail: cpilgrim@schoolcraft.edu. ferent across ethnic groups (Rowe et al, 1994). And even those studies that examine ethnic difference by comparing direct effects across groups still cannot fully consider whether mediation models are similar across ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility means that developmental models may be group specific, or vary across groups. A general developmental model needs to articulate broad and universal principles (Rowe, Vazsonyi, & Flannery, 1994) or at least allow for a diversity of pathways across groups (e.g., Steinberg, Darling, & Fletcher, 1995). With respect to the latter, Deater-Deckard, , using CDP data, found that physical discipline had different child behavioral correlates for European American children and African American children.…”
Section: Combinatory Modelsmentioning
confidence: 99%